Study of the Sensory, Chemical and Nutritional Properties of Cake Fortified with Black Lemon (Dried Lime) Extract - Al-Janabi, Shahad Khalid Hameed (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study aimed to know the chemical properties and evaluate some sensory and biological properties of cake fortified with dry black lemon extract. The study was conducted in the laboratories of the College of Agriculture/Department of Food Sciences/University of Tikrit. Dry black lemons were obtained from local markets in the city of Tikrit. Dry black lemon was obtained from local markets, and the laboratory cake was manufactured according to laboratory specifications. The aqueous and alcoholic extraction of the dry black lemon extract was carried out. The extract compounds were also identified using HPLC technology, and the animal feed of the experimental animals was fortified with dry black lemon extract. The study included four different treatments. The first treatment (A) was the control treatment without addition, the second treatment (A1) was the aqueous extract, the third treatment (A2) was the alcoholic extract, and the fourth treatment (A3) contained the artificial dye. The sensory evaluation results of the laboratory cake showed that treatment A3 was superior in terms of color, appearance, texture, and flavor, while A1 was superior to the other treatments in terms of softness and general acceptability. The results of HPLC diagnosis showed an abundance of b-pinene, y-terpinene and vitamin C compared to other compounds that appeared in relatively small quantities. As for the biological experiment, the results showed significant differences in weight for treatment B compared to control samples, and no significant differences were shown for cholesterol, HDL and LDL.